Is Solomon a Cipher of Messianic Hope? - Goswell, Gregory (The Evangelical quarterly, 2025)
The figure of Solomon is something of a conundrum in biblical theology. It might be supposed that the picture of his glorious reign supported reading Solomon as an antetype of Christ in 1 Kings 1-11, Psalm 72, and 2 Chronicles 1-9. However, Solomon proved to be a disappointment, preventing him from being a messianic precursor, and the celebrated aspects of his rule are better seen as presaging the consummated kingdom of God. This is in line with a robust theological reading of the Old Testament. What is prefigured in these three passages concerning the final kingdom of God is applicable to Jesus as the divine Son of God, whether the focus is the worldwide reach of his influence (1 Kings), the implementation of social justice (Psalm 72), or his acknowledged kingship symbolized by the temple (2 Chronicles).